2017
DOI: 10.1159/000458724
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Reactions during Double-Blind Placebo-Controlled Food Challenges

Abstract: Background: Severe anaphylactic symptoms can occur during oral food challenges (OFCs). Thus, high-risk patients (e.g., patients with a history of anaphylaxis or high antigen-specific immunoglobulin E [IgE] levels) must carefully undergo OFCs in hospitals. We attempted to identify the risk factors for severe symptoms during OFC testing among high-risk patients. Methods: We retrospectively evaluated patients' characteristics and severe symptoms that were experienced during a double-blind placebo-controlled food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 35 publications
4
56
1
1
Order By: Relevance
“…showed that a log-normal (AIC score 8139) was better than either a Weibull (8251) or logistic (10 143) distribution. The ED10 and ED50 derived from the log-normal distribution were 20 mg (95% CI: [15][16][17][18][19][20][21][22][23][24][25] and 300 mg (95% CI: 250-370), respectively. In view of the different age distributions of the Australian and European cohorts, analyses of these two subgroups were performed.…”
Section: Reaction Threshold During Peanut Ofcmentioning
confidence: 98%
“…showed that a log-normal (AIC score 8139) was better than either a Weibull (8251) or logistic (10 143) distribution. The ED10 and ED50 derived from the log-normal distribution were 20 mg (95% CI: [15][16][17][18][19][20][21][22][23][24][25] and 300 mg (95% CI: 250-370), respectively. In view of the different age distributions of the Australian and European cohorts, analyses of these two subgroups were performed.…”
Section: Reaction Threshold During Peanut Ofcmentioning
confidence: 98%
“…material, see www. karger.com/doi/10.1159/000486310) [20,21]. The severity of symptoms was based on the organ with the most severe symptoms.…”
Section: Dbpcfcmentioning
confidence: 99%
“…Treatments for provoked reaction were based on the European Academy of Allergy and Clinical Immunology's food allergy and anaphylaxis guidelines [9]. Anaphylaxis was defined according to World Allergy Organization Anaphylaxis Guidelines [10], and severity of symptoms was defined according to Japanese anaphylaxis guidelines [8,11].…”
Section: Oral Food Challengementioning
confidence: 99%